2004
DOI: 10.1002/ejoc.200300592
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Origin of 1,5‐anti Induction in Boron‐Mediated Aldol Reactions

Abstract: A model for the origin of selectivity in boron-mediated 1,5-anti-aldols is presented. This model involves π-stacking between the boron enolate and a remote aromatic ring. A short, facile method for the synthesis of the C-12 to C-22 segment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 38 publications
5
36
0
1
Order By: Relevance
“…The second critical aldol involves a 1,5-anti aldol between 5 and the product of 3 and 4, in which C11 would exist in the aldehyde oxidation state. The synthesis of an analog of (-)-5 (without the Et group) and 1,5-aldol studies have previously been reported by us, [18] in which we demonstrated that a Ͼ99:1 selectivity and 94 % yield could be achieved in this coupling. The synthesis of this analog was achieved in four steps in 33 % overall yield.…”
Section: Introductionsupporting
confidence: 54%
“…The second critical aldol involves a 1,5-anti aldol between 5 and the product of 3 and 4, in which C11 would exist in the aldehyde oxidation state. The synthesis of an analog of (-)-5 (without the Et group) and 1,5-aldol studies have previously been reported by us, [18] in which we demonstrated that a Ͼ99:1 selectivity and 94 % yield could be achieved in this coupling. The synthesis of this analog was achieved in four steps in 33 % overall yield.…”
Section: Introductionsupporting
confidence: 54%
“…Uma primeira proposta para explicar a seletividade 1,5-anti promovida por substituintes β-alcóxi foi feita por Hoberg em 2004, que sugeriu uma interação do tipo "π-stacking" entre o grupo protetor na posição β-carbonila do tipo benzílico e o enolato de boro no estado de transição cíclico 63 . No entanto, esta proposta não explica os elevados níveis de estereosseletividade 1,5-anti observados quando se utilizam grupos protetores como β-metóxi e éteres cíclicos.…”
Section: Origem Da Seletividade 15-antiunclassified
“…The strategy relies on the successful implementation of a 1,5-directed aldol reaction of a methyl ketone, generated by an aldol cascade terminated by the addition of 18 (acetone A major impediment to the implementation of this strategy was the lack of general methodologies for 1,5-stereoinduction using methyl ketones in the aldol reaction, perhaps owing to the great distance between stereodirecting group and the reaction site, as compared with 1,2-and 1,3-asymmetric induction [71]. Reports of 1,5-anti in the literature were previously limited to the use of boron enolates with β-alkoxy methyl ketones [72][73][74][75]. Even fewer descriptions of diastereoselective 1,5-syn aldol reactions using methyl ketones were found in the literature [76][77][78][79].…”
Section: Aldol Reactions Of β-Supersiloxy Methyl Ketonesmentioning
confidence: 99%